Analysing the Impact of Cultural Factors on the Success of Organizational Innovation in the Technology Industry - Shandana, Mahyash; Farid, Ahmad; Ramin, Qasim (Journal Social Humanity Perspective, 2024)
This paper analyzes how cultural influences affect organizational innovation success level by carrying out a qualitative case study in an organization in the technology industry. Whereas the previous literature has focused on structural forces and resource distribution as the main sources of innovation, this study identifies some of the cultural aspects that mediate and precondition the said mechanisms. Based on the results of the in-depth interviews followed by the thematic analysis, four culturally overlapping factors were identified: psychological safety, across the boundary collaboration, leadership empowerment and navigation of tensions between flexibility and control. Taken together this comprises the cultural infrastructure within which innovation practices are played out. The article presents the psychological safety as a strategic resource that facilitates rapid experimentation, collaboration across division of power as a tool of integrating knowledge, leadership empowerment as a culture signal to increase risk taking and recognition and that structural tensions cannot and should not be resolved. These results not only expand management theory with a conceptualization of culture as a micro foundation of dynamic capabilities and a demonstration of how the dynamics of the innovation paradoxes are negotiated socially at the team level. The findings have implications of cultural stewardship to practitioners: leaders need to deliberately foster a set of norms around the trust, inclusivity, and adaptive governance to maintain innovation through a rapidly-changing technological landscape. Despite being constrained by the parameters of a single-case study, the study provides transferable knowledge about the role of culture as the operating system of innovation, and that too, can create not only incremental changes but also transformative changes in the field of management of technology-driven organizations.